Effects of open and close kinetic chain exercises on the muscle strength and proprioception in healthy adults - Kasmalina Mohd
Exercise has been widely used as an adjunct therapy in musculoskeletal diseases and sports injuries such as osteoarthritis, patellofemoral pain syndrome, cruciate ligament injuries and reconstructions. Open and close kinetic chain exercises have been used and both have their own mechanism to improve clinical symptoms including reduce pain, improve muscle strength and proprioception. Many studies have been done to look into effect of open and close kinetic chain exercises in patients with these symptoms. However, there has been a lack of research data to compare the effectiveness of open and close kinetic chain exercise on muscle strength and proprioception. The purpose of this study is to compare the effects of open kinetic chain exercise (OKCE) and close kinetic chain exercise (CKCE) on strength of lower limb and proprioception of the joint in healthy adults. Thirty-three undergraduate students were included in this study and were randomly divided into OKCE and CKCE groups. Both groups had undergone 6 weeks rehabilitation programme of three sessions per week. The OKCE started static quadriceps contraction (SQE) exercise, inner range quads (IRQ) and straight leg raise (SLR) exercise. Meanwhile, the CKCE commenced lunge exercise, squat exercise and step exercise. Strength of quadriceps muscle and hamstring muscle in both OKCE and CKCE were recoded and analysed using an electromyography (EMG) device. Knee and ankle proprioception were determined by repositioning error test in sitting position. Based on independent t-test we found that there was no significant difference on quadriceps (p>0.05, p=0.602) and hamstring muscle strength (p>0.05, p=0.444) between OKCE and CKCE groups. Besides that, we found that there was no difference on knee (p>0.05, p=0.392) and ankle joint (p>0.05, p=0.643) proprioception of the limb although both groups showed slight improvement after 6 weeks of exercises. Therefore, a study with a longer duration is suggested to prove the effectiveness of the intervention.